Design and Implementation of A Patient-Doctor Monitoring System: A Review and A Telemedical Algorithmic Approach for Non-Invasive Post-Malaria-Diagnosis Monitoring - Kommey, Benjamin; Akwaboah, Akwasi Darkwah; Owusu-Akyaw, Josephine (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2018)
In an era where there is a globally concerted effort to improve healthcare especially in regions with endemic diseases like Sub-Saharan Africa, there have been major calls for real-time health data acquisition and reporting[1] to prompt health institutions and government to adequately plan and tackle such challenges. Data Acquistion is also very important as it will in the long run drive other future research work. Due to these eminent reasons, this paper seeks to review a number of situational reports, relevant projects and papers with proposed solutions or implemented prototypes that can be employed in monitoring the recovery and health status of patients that are diagnosed of Malaria. This paper also proposes an operational algorithm (based on the existing projects’ review) of a wearable embedded device in the form a flowchart to inspires device makers and innovators to design systems and devices to help in the fight against Malaria, which currently claims the lives of thousands annually. [2] The focus, though on Malaria because of its prevalence in the Sub-Saharan Africa, can be employed on other similar endemic diseases.